2020
DOI: 10.1093/arclin/acaa100
|View full text |Cite
|
Sign up to set email alerts
|

Teleneuropsychology for Monolingual and Bilingual Spanish-Speaking Adults in the Time of COVID-19: Rationale, Professional Considerations, and Resources

Abstract: Objective Neuropsychological assessments with monolingual Spanish and bilingual Spanish/English-speaking adults present unique challenges. Barriers include, but are not limited to, the paucity of test norms, uncertainty about the equivalence of translated neuropsychological tests, and limited proficiency in the provision of culturally competent services. Similar issues generalize to telephone- and video-based administration of neuropsychological tests or teleneuropsychology (TeleNP) with Hisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…At the broader system level, several articles pointed to changes in regulation and reimbursements that have enabled clinicians practicing in a wide range of settings to quickly adopt e-mental health solutions for both existing and new patients struggling with the pandemic’s impact [ 29 - 31 , 52 , 67 ]. Patel et al identified a number of local and national collaborative approaches to care that have been developed since COVID-19, such as “Webinars for Nursing Homes” that have linked palliative care, geriatrics, and psychiatric old-age services in Ireland through Project ECHO AIIHPC (Extension for Community Healthcare Outcomes, All Ireland Institute of Hospice and Palliative Care) to help nursing home staff improve their knowledge of e-mental health tools [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the broader system level, several articles pointed to changes in regulation and reimbursements that have enabled clinicians practicing in a wide range of settings to quickly adopt e-mental health solutions for both existing and new patients struggling with the pandemic’s impact [ 29 - 31 , 52 , 67 ]. Patel et al identified a number of local and national collaborative approaches to care that have been developed since COVID-19, such as “Webinars for Nursing Homes” that have linked palliative care, geriatrics, and psychiatric old-age services in Ireland through Project ECHO AIIHPC (Extension for Community Healthcare Outcomes, All Ireland Institute of Hospice and Palliative Care) to help nursing home staff improve their knowledge of e-mental health tools [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The low resolution of the screens can affect the discrimination of colors present in the tests. Finally, the quality of the audio can lead to loss of information or interruption 18 . These situations were addressed through the recording of the assessments and subsequent reviews.…”
Section: Dement Neuropsycholmentioning
confidence: 99%
“…However, the development of TNP in Latin America (LA) is still in its incipient, and the assessment of CD with the brief instruments through telehealth formats in rural seniors has not been conducted in the region 17 . Few studies have analyzed the reliability and validity of neuropsychological tests in the telehealth context among Latin or Hispanic people 18 ; mainly in preclinical phases of dementia, such as mild cognitive impairment (MCI).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant limitation of our work is that the studies from which we based our recommendations were mostly written in the English language. This is due to the lack of studies on Spanish-speaking populations from Latin America ( Arias et al., 2020 ). However, studies on Spanish-speaking populations in the United States and in Spain support the applicability of teleNP in Spanish ( Franco, Bernardo-Ramos, & Soto-Pérez, 2012 ).…”
Section: Limitationsmentioning
confidence: 99%